1997
DOI: 10.1183/09031936.97.10050994
|View full text |Cite
|
Sign up to set email alerts
|

Effect of roxithromycin on airway responsiveness in children with bronchiectasis: a double-blind, placebo-controlled study

Abstract: Increased airway responsiveness (AR) is frequently associated with bronchiectasis. Roxithromycin is a new semisynthetic macrolide antibiotic that also has anti-inflammatory activities. This study was designed to see whether roxithromycin could favourably alter the degree of AR in patients with bronchiectasis and increased AR. Twenty five children with bronchiectasis, who had an increased AR (defined as a provocative concentration of methacholine causing a 20% fall in forced expiratory volume in one second (FEV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
107
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(111 citation statements)
references
References 29 publications
(36 reference statements)
0
107
0
4
Order By: Relevance
“…Administration of low-dose EM, probably by the inhibition of glycoconjugate release [18], reduces sputum production in patients with bronchorrhoea [19] and DPB [7,9]. Low-dose EM, with unclear mechanisms, also reduces airway responsiveness in patients with bronchiectasis [20]. A recent study by the authors has shown that an 8-week administration period of low-dose EM (500 mg b.i.d) significantly reduced sputum volume and improved lung function in steady state severe idiopathic bronchiectasis.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of low-dose EM, probably by the inhibition of glycoconjugate release [18], reduces sputum production in patients with bronchorrhoea [19] and DPB [7,9]. Low-dose EM, with unclear mechanisms, also reduces airway responsiveness in patients with bronchiectasis [20]. A recent study by the authors has shown that an 8-week administration period of low-dose EM (500 mg b.i.d) significantly reduced sputum volume and improved lung function in steady state severe idiopathic bronchiectasis.…”
Section: Discussionmentioning
confidence: 99%
“…Only two were randomised double-blind placebo-controlled trials. KOH et al [37] showed a significant decrease in airway responsiveness to methacholine in children with bronchiectasis (and increased airway responsiveness) who received roxithromycin (n513) for 12 weeks compared to controls (n512). There was no change in spirometric results, but, by 6 weeks, significant improvements in sputum purulence scores were observed in the treatment arm.…”
Section: Bronchiectasismentioning
confidence: 99%
“…According to the vicious cycle hypothesis, if infection is the primary driver of airway inflammation, bacterial clearance through the use of short-or long-term antibiotic therapy would be expected to reduce airway inflammation, allow airway healing and modify the long-term course of the disease. Until very recently, the role of macrolide therapy in non-CF bronchiectasis had only been investigated in studies that were small, of short duration and did not assess clinical relevant outcomes, such as pulmonary exacerbations and quality of life [44][45][46][47]. In a recently published, randomised, double-blind, placebo-controlled trial, 141 patients (aged o18 years) with a diagnosis of bronchiectasis as defined by HRCT and at least one pulmonary exacerbation requiring antibiotic treatment in the previous year, were assigned to receive azithromycin 500 mg three times per week or placebo for 6 months in a 1:1 ratio [48].…”
Section: Non-cf Bronchiectasismentioning
confidence: 99%